A new stress sensor and risk factor for suicide: the T allele of the functional genetic variant in the GABRA6 gene. Issue 1 (December 2017) - Gonda, Xenia; Sarginson, Jane; Eszlari, Nora; Petschner, Peter; Toth, Zoltan; Baksa, Daniel; Hullam, Gabor; Anderson, Ian; Deakin, J.; Juhasz, Gabriella; Bagdy, Gyorgy
Abstract Low GABA transmission has been reported in suicide, andGABRA6 rs3219151 T allele has been associated with greater physiological and endocrine stress response in previous studies. Although environmental stress also plays a role in suicide, the possible role of this allele has not been investigated in this respect. In our present study effect of rs3219151 ofGABRA6 gene in interaction with recent negative life events on lifetime and current depression, current anxiety, as well as lifetime suicide were investigated using regression models in a white European general sample of 2283 subjects. Post hoc measures for phenotypes related to suicide risk were also tested for association with rs3219151 in interaction with environmental stress. No main effect of theGABRA6 rs3219151 was detected, but in those exposed to recent negative life eventsGABRA6 T allele increased current anxiety and depression as well as specific elements of suicide risk including suicidal and death-related thoughts, hopelessness, restlessness and agitation, insomnia and impulsiveness as measured by the STOP task. Our data indicate that stress-associated suicide risk is elevated in carriers of theGABRA6 rs3219151 T allele with several independent markers and predictors of suicidal behaviours converging to this increased risk.